Demonstration of a Broadband Very Long Baseline Interferometer System: A New Instrument for High‐Precision Space Geodesy. Issue 10 (4th October 2018) - Niell, A.; Barrett, J.; Burns, A.; Cappallo, R.; Corey, B.; Derome, M.; Eckert, C.; Elosegui, P.; McWhirter, R.; Poirier, M.; Rajagopalan, G.; Rogers, A.; et al.
Abstract: A prototype broadband geodetic very long baseline interferometry system has been implemented, and measurements of the baseline length over approximately two years, between December 2014 and January 2017, have been made in the process of exercising the system, developing operational procedures, and assessing geodetic precision for the new broadband observing concept. In addition to developing a broadband signal chain and installing the instrumentation on both a new 12‐m antenna at the Goddard Geophysical and Astrophysical Observatory and the 18‐m Westford antenna at the Massachusetts Institute of Technology Haystack Observatory, it was necessary to develop new correlation and analysis procedures to process the four‐band, dual‐linear‐polarization data. A geodetic analysis of the data from 19 sessions that were observed during this period yielded a weighted root‐mean‐square deviation of the baseline length residuals about the weighted mean of 1.6 mm. These results validate several of the expectations set forth for the vision of the next‐generation geodetic very long baseline interferometry system. Key Points: We demonstrated the first broadband VLBI systems for high‐precision space geodesy We developed procedures for data acquisition and analysis of the broadband geodetic data We generated the first VGOS baseline length time series